Generative artificial intelligence as powered writing tools in academic writing - Exequiel B. Gonzaga; Nasrah A. Manguda; Rodelina B. Tado; Ivy F. Amante; Rovy M. Banguis; Shem A. Cedeño; Joveth Jay D. Montaña; Jai Rondo S. Apilar (IAES International Journal of Artificial Intelligence (IJ-AI), 2026)
Generative Artificial Intelligence (GAI) as a writing tool is rampantly developing and attracting attention in academic writing. This study aimed to analyze the use of GAI as an AI-powered writing tool in academic writing among college students. By using a mixed method design with criterion purposive sampling, the researchers gathered the data from eighty students through a survey and selected individuals from all year levels underwent interviews. Descriptive statistics and thematic analysis were used to analyze their perceptions and integration of GAI tools. The result reveals mainly high levels of perception: knowledge perception, “High”; frequency and extent of use, “Average”; impact on academic writing, “High”; and integration with human writers, “High”. The study further identified that the students integrate GAI writing tools to improve writing quality, efficiency, and productivity. On the other hand, their disadvantages include over-reliance on GAI tools and inaccuracy issues. The findings suggest that GAI tools integration improves academic writing, but negatively impacts the students’ character. This study stresses the importance of moderation in using GAI writing tools and recommends looking further into the different ways of effective integration.